Methanol Extract Lotion of Tagetes erecta L. Flower as A Repellent Against Culex quinquefasciatus - Siti Maisaroh; Tri Wulandari Kesetyaningsih (Universitas Muhammadiyah Yogyakarta, 2021)
Most Lymphatic Filariasis is transmitted by Culex quinquefasciatus. DEET is effective to repel mosquitoes, but it has side effects. Marigold (Tagetes erecta L.) flower contains flavonoids and terpenoids which are potential repellents. This study aims to determine the effectiveness of the methanol extract lotion of T. erecta as a repellent against Cx quinquefasciatus. This is an experiment with a posttest-only control group design. There were seven concentration groups, including control and treatment groups of 2%, 4%, 8%, 16%, and 32% extract. The lotion was applied to the skin of the guinea pig. There were 25 female mosquitoes per cage for each experiment. One Way Anova and Probit used to analyze the data. The result showed that there was a significant difference among the research groups (p<0.01), of which 16% and 32% have significant values (p 0.106 and 0.350 compared with DEET respectively). RC50 and RC90 are in 11.078% and 32.131% respectively, with RT50 and RT90 at the hour of 2.398 and 1.496 respectively. It concluded that the methanol extract lotion of T. erecta was effective to repel Cx quinquefasciatus at 16% concentration, and potency against 50% and 90% are in 11.078% and 32.131%, at the hour of 2.398 and 1.496 respectively.